Structural Analysis, Characterization, and First-Principles Calculations of Bismuth Tellurium Oxides, Bi6Te2O15 - Sun Woo Kim; Hong Young Chang (Crystals, 2023)
A single crystal of Bi6Te2O15 was obtained from the melt of the solid-state reaction of Bi2O3 and TeO3. Bi6Te2O15 crystallizes in the Pnma space group (No. 62) and exhibits a three-dimensional network structure with a =10.5831(12) Å, b = 22.694(3) Å, c = 5.3843(6) Å, α = β = γ = 90°, V = 1293.2(3) Å3, and Z = 4. The structure was determined using single-crystal X-ray diffraction. An asymmetric unit in the unit cell, Bi3Te1O7.5, uniquely composed of four Bi3+ sites, one Te6+ site, and nine O2− sites, was solved and refined. As a bulk phase, Bi6Te2O15 was also synthesized and characterized using powder X-ray diffraction (XRD), infrared (FT-IR) spectrometry, and the thermogravimetric analysis (TGA) method. Through bond valence sum (BVS) calculations from the single crystal structure, Bi and Te cations have +3 and +6 oxidation numbers, respectively. Each Bi3+ cation forms a square pyramidal structure with five O2− anions, and a single Te6+ cation forms a six-coordinated octahedral structure with O2− anions. Since the lone-pair electron (Lp) of the square pyramidal structure, [BiO5]7−, where the Bi+ cation occupies the center of the square base plane, exists in the opposite direction of the square plane, the asymmetric environments of all four Bi3+ cations were analyzed and explored by determining the local dipole moments. In addition, to determine the extent of bond strain and distortion in the unit cell, which is attributed to the asymmetric environments of the Bi3+ and Te6+ cations in Bi6Te2O15, bond strain index (BSI) and global instability index (GII) were also calculated. We also investigated the structural, electronic, and optical properties of the structure of Bi6Te2O15 using the full potential linear augmented plane wave (FP-LAPW) method and the density functional theory (DFT) with WIEN2k code. In order to study the ground state properties of Bi6Te2O15, the theoretical total energies were calculated as a function of reduced volumes and then fitted with the Birch–Murnaghan equation of state (EOS). The band gap energy within the modified Becke–Johnson potential with Tran–Blaha parameterization (TB-mBJ) revealed a value of 3.36 eV, which was higher than the experimental value of 3.29 eV. To explore the optical properties of Bi6Te2O15, the real and imaginary parts of the dielectric function, refraction index, optical absorption coefficient, reflectivity, the real part of the optical conductivity extinction function, and the energy loss function were also calculated.